The Relationship Between The Leadership Style Of Transformational Principals And The Performance Of Educational Staff At Smk Sasmita Jaya 1, South Tangerang - Kinanti, Jelita Irna; Atmojo, Kunto; Wibowo, Hadi Mulyo (Doctoral Program of Social Science Pasundan University, 2025)
This study aims to examine the relationship and how big the relationship is between the transformational principal's leadership style and the performance of educational staff at SMK Sasmita Jaya 1 Tangerang Selatan. Transformational leadership style is measured through charisma, inspiring motivation, attention to individuals, and intellectual stimulation. Meanwhile the performance of educational staff is measured using four indicators, namely work quality, work quantity, punctuality, and responsibility. This study uses a quantitative correlational method with a total number of respondents of 71 people taken by total sampling. Data collection using a questionnaire with a Likert scale, then analyzed using the Pearson correlation test has a value of 0.531 and a coefficient of determination (R²) has a value of 28.2%. The results of the study showed that the results of the Pearson correlation test showed a significant relationship between the transformational principal's leadership style and the performance of educational staff, that the two variables had a moderate and positive relationship. While the results of the coefficient of determination show that the performance of educational staff is influenced by the transformational principal's leadership style variable. This study is expected to be a consideration for increasing the effectiveness of principal leadership and as a basis for further research.